Epidemiological Evaluation of Suicidal Deaths due to Organophosphorus Compound Poisoning - Rahman, Md Fahmidur; Islam, Md Shamsul; Uddin, N M Minhaz; Alam, Md Shah; Poly, Tahmina Begum; Nurunnabi, Mohammad (Journal of Monno Medical College, 2023)
Background: One of the most widespread suicide methods, especially emerging in developing countries like Bangladesh, is poisoning. Organophosphorus compound (OPC) is a common chemical used for self-poisoning that is also inexpensive and easily accessible. Objectives: To evaluate the demography of suicidal deaths due to OPC poisoning. Methods: This was a retrospective study with the departmental records of autopsy among deaths due to OPC poisoning. The study was carried out to ascertain the epidemiological evaluation of 242 OPC poisoning suicidal deaths during January, 2016 to December, 2017 at the mortuary of Sylhet MAG Osmani Medical College, Bangladesh. Results: Majority of the victims (184, 76.03%) were below 40 years of age and females were predominant (142, 58.67%). Most of the victims resided in Companygonj (47, 19.42%), followed by Kotwali (40, 16.52%), and Gowainghat (35, 14.52%) of Sylhet district. Most of the dead bodies (192, 79.33%) were brought to the morgue under Kotwali police station. The most common (218, 90.08%) cause of death was respiratory failure. Conclusion: Suicide with OPC was the most common in younger women. Establishment of national suicide surveillance is now a time demanded step and responsible authority should take some necessary steps to address it. Journal of Monno Medical College, June 2023; 9 (1): 20-23